eCM 2010
DOI: 10.22203/ecm.v019a08
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dynamic loading improves the mechanical properties of chondrogenic mesenchymal stem cell-laden hydrogel

Abstract: Mesenchymal stem cells (MSCs) are an attractive cell source for cartilage tissue engineering given their ability to undergo chondrogenesis in 3D culture systems. Mechanical forces play an important role in regulating both cartilage development and MSC chondrogenic gene expression, however, mechanical stimulation has yet to enhance the mechanical properties of engineered constructs. In this study, we applied long-term dynamic compression to MSC-seeded constructs and assessed whether varying pre-culture duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
176
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(191 citation statements)
references
References 48 publications
14
176
1
Order By: Relevance
“…Likewise, bovine MSCs show a sharp decrease with age in cartilage matrix-forming capacity that is more severe than reported for human MSCs in this same format [5]. Overall, at each age, and under ideal conditions (absence of TGF for chondrocytes, presence of TGF for MSCs), bovine chondrocytes in pellet culture produce more GAG and collagen than MSCs, consistent with our previous findings [17,22,33]. Taken together, when considering an autologous cellbased tissue engineering strategy for cartilage repair, age must be an important consideration.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, bovine MSCs show a sharp decrease with age in cartilage matrix-forming capacity that is more severe than reported for human MSCs in this same format [5]. Overall, at each age, and under ideal conditions (absence of TGF for chondrocytes, presence of TGF for MSCs), bovine chondrocytes in pellet culture produce more GAG and collagen than MSCs, consistent with our previous findings [17,22,33]. Taken together, when considering an autologous cellbased tissue engineering strategy for cartilage repair, age must be an important consideration.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore identifying expansion and differentiation conditions that promote a more chondrogenic phenotype is critical to enhancing their utility for cartilage tissue engineering applications. Differentiation conditions that have been shown to promote the chondrogenic potential of MSCs include a low oxygen (5%) microenvironment (Khan et al 2007;Buckley et al 2010a;Meyer et al 2010), various combinations of growth factors (Mastrogiacomo et al 2001;Sakimura et al 2006;Hennig et al 2007;Diekman et al 2010;Buxton et al 2011) and mechanical signals (Huang et al 2005;Mauck et al 2007;Huang et al 2010a;Huang et al 2010b;Kelly and Jacobs 2010;Li et al 2010; Thorpe et al 2010;Haugh et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was thus to improve the predictive capacity of the model by including a series of rules whereby the local mechanical environment affected the fate of cartilage. Based on the findings of a number of in vitro studies which have shown that mechanical loading can either prevent hypertrophy and endochondral ossification of cartilage [12][13][14][15][16] , or promote the formation of fibrocartilage 18,19 , it was hypothesised that the fate of the cartilage that forms within an osteochondral defect depends on both oxygen availability and the local mechanical environment. It was postulated that hypertrophy was supressed by appropriate magnitudes of local strain, while fibrocartilage formed in regions where the local strain was excessively high.…”
Section: Discussionmentioning
confidence: 99%
“…In general it has been shown that active loading applied at an early stage leads to the formation of fibrous tissue and fibrocartilage, while continuous passive motion has been shown to result in the formation of hyaline cartilage 7,8,11 . A number of in vitro studies, where the levels of mechanical stimulation can be carefully controlled using bioreactor systems, have also demonstrated how compressive loading can regulate chondrogenesis of MSCs [12][13][14][15][16] . For example, Thorpe et al 17 showed that dynamic compressive loading of chondrogenically primed MSCs led to the upregulation of chondrogenic markers and also inhibited terminal differentiation and mineralisation.…”
Section: Introductionmentioning
confidence: 99%